Transcriptional profiling unravels potential metabolic activities of the olive leaf non-glandular trichome - Koudounas, Konstantinos; Manioudaki, Maria :; Kourti, Anna; Banilas, Georgios; Hatzopoulos, Polydefkis (Frontiers in Plant Science, 2015)
The olive leaf trichomes are multicellular peltate hairs densely distributed mainly at the lower leaf epidermis. Although non-glandular, they have gained much attention since they significantly contribute to abiotic and biotic stress tolerance of olive leaves. The exact mechanisms by which olive trichomes achieve these goals are not fully understood. They could act as mechanical barrier but they also accumulate high amounts of flavonoids among other secondary metabolites. However, little is currently known about the exact compounds they produce and the respective metabolic pathways. Here we present the first EST analysis from olive leaf trichomes by using 454-pyrosequencing. A total of 5,368 unigenes were identified out of 7,258 high quality reads with an average length of 262 bp. Blast search revealed that 27.5% of them had high homologies to known proteins. By using Blast2GO, 1,079 unigenes (20.1%) were assigned at least one Gene Ontology (GO) term. Most of the genes were involved in cellular and metabolic processes and in binding functions followed by catalytic activity. A total of 521 transcripts were mapped to 67 KEGG pathways. Olive trichomes represent a tissue of highly unique transcriptome as per the genes involved in developmental processes and the secondary metabolism. The results indicate that mature olive trichomes are trancriptionally active, mainly through the potential production of enzymes that contribute to phenolic compounds with important roles in biotic and abiotic stress responses.